CD7 is expressed on a subset of normal CD34‐positive myeloid precursors. (4th July 2018) - Kriegsmann, Katharina; Löffler, Harald; Eckstein, Volker; Schulz, Renate; Kräker, Sandra; Braun, Ute; Luft, Thomas; Hegenbart, Ute; Schönland, Stefan; Dreger, Peter; Krämer, Alwin; Ho, Anthony D.; et al.
Abstract: Objective: To improve monitoring of myeloid neoplasms by flow cytometry‐based minimal residual disease (MRD) analysis, we analyzed the significance of leukemia‐associated immunophenotype (LAIP) markers in 44 patients. Methods: In a pilot study cohort, peripheral blood or bone marrow samples from 13 patients with myeloid neoplasms and one case of B lymphoblastic leukemia in complete hematologic remission after allogeneic bone marrow or stem cell transplantation were subjected to selection for leukemia‐specific phenotypes by fluorescence‐activated cell sorting using individual marker combinations, followed by PCR‐based chimerism analysis. Results: The feasibility of this method could be demonstrated, with selection being successful in 12 cases, including two cases where mixed chimerism was found exclusively in sorted cells. Interestingly, four specimens displayed full donor chimerism in cells expressing the presumably aberrant combination CD34 + /CD7 + . Further analyses, including assessment of an independent cohort of 25 patients not affected by neoplastic bone marrow infiltration, revealed that normal myeloid precursors usually include a population coexpressing CD34, CD13, CD33, and CD7. Conclusion: We conclude that the combination CD34 + /CD7 + might not be suitable as an LAIP for MRD diagnostics and that a subset of normal myeloid precursors in the bone marrow expresses CD7.